Towards the internationalization of Cuban medical education: the role of the Common European Framework of Reference - Nodarse-Álvarez, Juan Carlos; Calderón-González , Leys Lubia; Navarro-Brito , Liset (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
In the context of the globalization of medical knowledge and the growing need for internationalization in the training of healthcare professionals, this article argues for the strategic relevance of implementing the Common European Framework of Reference for Languages ​​(CEFR) in Cuban medical universities. It highlights that linguistic competence, particularly in English as the lingua franca of science, has ceased to be an optional complement and has become a fundamental pillar of academic, research, and clinical excellence. The CEFR is presented not only as an assessment tool but also as an international standard that guarantees three key benefits for Cuban higher medical education: first, direct, critical, and ongoing access to high-impact scientific literature, enabling professionals to understand and independently utilize global biomedical advances; second, the development of essential communicative and intercultural competencies for modern medical practice, which transcend grammar to include cultural sensitivity in diverse contexts; and third, the facilitation of academic mobility and international collaboration by providing globally recognized certifications that serve as professional passports. Finally, five concrete lines of action are proposed for the systematic integration of the CEFR into institutional educational policies, including curriculum alignment, teacher training, implementation of internal evaluation systems, promotion of international mobility and the creation of specialized language centers for health sciences, emphasizing that this adoption constitutes an investment in human capital to project Cuban medicine on the global stage.